2007
DOI: 10.1057/palgrave.abm.9200228
|View full text |Cite
|
Sign up to set email alerts
|

International Expansion Path, Speed, Product Diversification and Performance Among Emerging-Market MNEs: Evidence from Asia-Pacific Multinational Companies

Abstract: The purpose of this study is to provide an integrated framework that conceptualizes multifaceted antecedents pertaining to international expansion of emerging-market businesses in relation to firm performance. This paper develops multiple-item measures of multiple dimensions to clarify how internationalization path, expansion speed, product diversification and geographic scope affect emergingmarket multinational enterprise (MNE) performance in a sample of 115 AsiaPacific MNEs over the period 1998-2002. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 29 publications
(43 reference statements)
3
42
0
13
Order By: Relevance
“…Os estudos mais recentes têm encontrado resultados não lineares para a relação entre o grau de internacionalização e o desempenho, indicando que as EMNs obtêm tanto benefícios quanto custos em seu processo de internacionalização (Chang, 2007;Contractor et al, 2003;Gomes & Ramaswamy, 1999;Lu & Beamish, 2004). Nesse sentido, Ruigrok e Wagner (2003) argumentam que "a internacionalização, por si só, não é uma condição suficiente para um desempenho superior, de modo que hipotetizar uma relação monotônica linear entre internacionalização-desempenho não consiste no melhor caminho à construção da teoria" (p. 68).…”
Section: O Interjogo Entre Benefícios E Custos Da Internacionalizaçãounclassified
See 2 more Smart Citations
“…Os estudos mais recentes têm encontrado resultados não lineares para a relação entre o grau de internacionalização e o desempenho, indicando que as EMNs obtêm tanto benefícios quanto custos em seu processo de internacionalização (Chang, 2007;Contractor et al, 2003;Gomes & Ramaswamy, 1999;Lu & Beamish, 2004). Nesse sentido, Ruigrok e Wagner (2003) argumentam que "a internacionalização, por si só, não é uma condição suficiente para um desempenho superior, de modo que hipotetizar uma relação monotônica linear entre internacionalização-desempenho não consiste no melhor caminho à construção da teoria" (p. 68).…”
Section: O Interjogo Entre Benefícios E Custos Da Internacionalizaçãounclassified
“…Seguindo comportamento semelhante aos resultados verificados em estudos com EMNs de economias desenvolvidas, observa-se que a relação internacionalização-desempenho no universo de EMNs de economias em desenvolvimento também tem considerado os custos e benefícios inerentes à estratégia de internacionalização: (a) relação em forma de U (Contractor, Kumar, & Kundu, 2007;Thomas, 2006); (b) relação em forma de S horizontal (Chang, 2007); e (c) relação em forma de U invertido (H. Chen & Hsu, 2010;Chiao & Yang, 2011 Como pode ser visto na Figura 1, a variável independente, grau de internacionalização, é formada por três outras variáveis: (a) a razão dos ativos externos em relação aos ativos totais da empresa; (b) a razão das vendas externas em relação às vendas totais da empresa; e (c) a razão dos funcionários externos em relação aos funcionários totais. Assim, essas três variáveis formam juntas o construto grau de internacionalização.…”
Section: O Interjogo Entre Benefícios E Custos Da Internacionalizaçãounclassified
See 1 more Smart Citation
“…Intraregional geographic diversification allows born-globals to expand their product market so they can break even more rapidly and recoup their investments (Chang, 2007;Rugman & Verbeke, 2004).…”
Section: Home Industry Conditions and Geographic Diversificationmentioning
confidence: 99%
“…The increase in the DOI level means that companies are progressing in the internationalization process and has an impact on the export performance of the companies (Pangarkar, 2008). When subanalyses of DOI elements are conducted, it would be observed that there is a correlation between the performance and the factors of FSTS (Riahi -Balkaoui, 1998, Nehrt, 1999, Ruigrok et al, 2007Loncan and Nique, 2010), FATA (Sullivan,1994;Ramaswamy et al, 1996;Nehrt, 1999;Kennelly and Lewis, 2001), PDIO (Conway and Swift, 2000;Evans et al, 2000;Loncan and Nique, 2010), TMIE (Sua'rez-Ortega and A'lamoVera, 2005), FETE (Contractor et al, 2003;Hassel et al, 2003;Chang, 2007;Greve et al, 2009;Nielsen, 2010;Zhang and Toppinen, 2011), OSTS (Sullivan,1994;Ramaswamy et al, 1996;Kennelly and Lewis, 2001). Several correlations such as S (Lu and Beamish, 2004), J and U (Contractor et al, 2003), reverse U (Elango and Sethi, 2007), positive linear, positive decreasing (López-Morales and Gómez-Casas, 2014) between DOI and performance have been established by various researchers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%